2020
DOI: 10.1186/s12885-020-06967-2
|View full text |Cite
|
Sign up to set email alerts
|

Testing for causality between systematically identified risk factors and glioma: a Mendelian randomization study

Abstract: Background: Whilst epidemiological studies have provided evidence of associations between certain risk factors and glioma onset, inferring causality has proven challenging. Using Mendelian randomization (MR), we assessed whether associations of 36 reported glioma risk factors showed evidence of a causal relationship. Methods: We performed a systematic search of MEDLINE from inception to October 2018 to identify candidate risk factors and conducted a meta-analysis of two glioma genome-wide association studies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…There was no difference between family history of cancer and gliomas, perhaps because this association is more common in certain types of syndromes, such as Li Fraumeni, Turcort, neuro bromatosis, among others [17], which did not occur in this study. There was also no association between gliomas and smoking or alcohol consumption; however, some authors reported a higher risk for high-grade gliomas in cases of excessive smoking [18] and alcohol use [19,20]. High-grade gliomas occur in older patients [14][15][16], corroborating the present study results, as cellular aging increases immunological senescence, telomere shortening, chronic in ammation with antigenic stimulation, genomic instability, and mutations forming more aggressive neoplasms such as high-grade gliomas [17].…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference between family history of cancer and gliomas, perhaps because this association is more common in certain types of syndromes, such as Li Fraumeni, Turcort, neuro bromatosis, among others [17], which did not occur in this study. There was also no association between gliomas and smoking or alcohol consumption; however, some authors reported a higher risk for high-grade gliomas in cases of excessive smoking [18] and alcohol use [19,20]. High-grade gliomas occur in older patients [14][15][16], corroborating the present study results, as cellular aging increases immunological senescence, telomere shortening, chronic in ammation with antigenic stimulation, genomic instability, and mutations forming more aggressive neoplasms such as high-grade gliomas [17].…”
Section: Discussionmentioning
confidence: 99%
“…In another branch of causal discovery, Mendelian randomization (MR) uses genetic variants, such as single-nucleotide polymorphisms (SNPs), that are robustly associated with an exposure as proxies for the risk factor of interest [ 154 ], therefore eliminating confounding and reverse causation effects between the exposure of interest and outcome. Howell et al (2020) [ 155 ] used MR to assess the causal relationship of associations of 36 reported glioma risk factors obtained from a systematic MEDLINE search on observational epidemiology studies. A meta-analysis of two glioma genome-wide association studies (GWASs) was then performed, and a two-sample MR analysis using the GWAS exposure and outcome datasets investigated the causal relationships between the risk factors identified and glioma incidence.…”
Section: Network Discovery In Glioblastomamentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most lethal type of glioma according to the grade of malignancy, with an average survival time of 12 to 14 months and a five-year survival rate of only 4% to 5% ( 3 , 4 ). The mortality rate of glioma has been stable at 4-5/100,000, ranking among the top 10 in tumour mortality ( 5 ). At present, the treatment of glioma is mainly by surgery, supplemented by radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%